School Mapping And The Universalization Of Basic Education In Imo State, Nigeria - Obasi, Kenneth K.; Madu, Onyewuchi M. (Advances in Social Sciences Research Journal, 2018)
The study investigated school mapping and the universalization of basic education in Imo State. Two research questions and two hypotheses guided the study. The study adopted the descriptive survey design. The population of the study was 1,777 consisting of 1,276 Head Teachers, 216 staff of the Imo State Universal Basic Education Board (IMSUBEB) and 285 staff of the Ministry of Education (MoE). The sample size was 327 which is 18.4% of the population. This consisted of 193 head teachers, 64 staff of IMSUBEB and 70 staff of MoE. These were selected using the stratified random sampling technique and the simple random sampling technique respectively. A questionnaire titled: School Mapping and the Universalization of Basic Education Questionnaire (SMUBEQ) was used for data collection. It was validated by experts in Educational Management and Measurement and Evaluation. The reliability was determined through the use of test-retest approach, using the Pearson’s Product Moment Correlation Statistics with a reliability index of 0.84. Mean and Standard Deviation were used to analyze the data while z-test statistics was used to test the hypotheses at 0.05 level of significance. The findings revealed among others that the level of primary school mapping since the implementation of UBE programme was low because it was carried out only on sampled subzones. The study recommended among others that the Government should as a matter of necessity carry out comprehensive school mapping to cater for the demand effect of the UBE programme.